Comparison of the gastrointestinal bacterial microbiota between dairy cows with and without mastitis - Guo, Chunyan; Liu, Jingjing; Wei, Yong; Du, Wen; Li, Shengli (Frontiers in Microbiology, 2024)
Mastitis causes significant losses in the global dairy industry, and the health of animals has been linked to their intestinal microbiota. To better understand the relationship between gastrointestinal microbiota and mastitis in dairy cows, we collected blood, rumen fluid, and fecal samples from 23 dairy cows, including 13 cows with mastitis and 10 healthy cows. Using ELISA kit and high-throughput sequencing, we found that cows with mastitis had higher concentrations of TNF-α, IL-1, and LPS than healthy cows (p < 0.05), but no significant differences in microbiota abundance or diversity (p > 0.05). Principal coordinate analysis (PCOA) revealed significant differences in rumen microbial structure between the two groups (p < 0.05), with Moryella as the signature for rumen in cows with mastitis. In contrast, fecal microbial structure showed no significant differences (p > 0.05), with Aeriscardovia, Lactococcus, and Bacillus as the signature for feces in healthy cows. Furthermore, the results showed distinct microbial interaction patterns in the rumen and feces of cows with mastitis compared to healthy cows. Additionally, we observed correlations between the microbiota in both the rumen and feces of cows and blood inflammatory indicators. Our study sheds new light on the prevention of mastitis in dairy cows by highlighting the relationship between gastrointestinal microbiota and mastitis.